Setorização no Desenho de Rotas - aplicação ao transporte de utentes não urgentes entre as suas residências e um centro hospitalar - Tiago Gaspar Pereira (2019)
The importance and necessity of top management-related decision support systems that assist in routing and sectorization problems is increasingly evident.In this sense, in this dissertation, several solutions are addressed to solve these problems, with regard to the concrete case study on patient collection, as well as their transportation from their residences to the hospital center in question, where the target is the region of Porto, where it is ideal to obtain the shortest possible distance (it is also possible to analyze in terms of minimization of costs or resources), obeying a set of restrictions, which may be specific physical or psychological characteristics of each patient, geographical location of the users in question, among others.Hence, heuristics and metaheuristics are born, so that it can include any kind of conditions that are necessary for the problem in question.Thus, it is intended to segment the Porto area, for a set of patients, by location, as well as defining the best route to be traveled, taking into account the vehicle's collection and transportation capacity and possible restrictions which relate to the patient itself.